Durasi Bermain dan Kuantitas Tidur Pada Anak dengan Talasemia: Studi Korelasi - Feriana Ira Handian; Neni Maemunah; Wahidyanti Rahayu Hastutiningtyas; Triputra Daud Umbu Tonga (Journal of Health (JOH))
Children with thalassemia are different from other kids in terms of their physical and mental health. Sleep and physical exercise, particularly playing, are important factors to consider while improving one's quality of life, especially physical well-being. A decent quality of life long-term impacts physical, mental, and emotional well-being, allowing children with thalassemia to live. This study aims to determine the relationship between play duration and sleep quantity in children with thalassemia. This study employed a cross-sectional design. In June and August of 2024, 30 parents of children aged 1 to 15 in Malang City with thalassemia were surveyed to get information on the duration of sleep and playtime. With differences in play hours of 1–15 hours and sleep hours of 7–21 hours, the Pearson Correlation analysis revealed a significant association between play duration and sleep quantity (p = 0.014). Thalassemia children have varying sleep durations, reflecting the complexity of the condition and varying care requirements. The general well-being of children with thalassemia depends on interventions enhancing sleep quality, such as emotional support and physical symptom treatment.